2021
DOI: 10.3390/ani11102926
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Analysis of the Helminth Community of the Wood Mouse, Apodemus sylvaticus, along an 18-Year Post-Fire Regeneration Period in a Mediterranean Ecosystem

Abstract: The role of helminths of the wood mouse, Apodemus sylvaticus, as biological indicators of the post-fire regeneration process in Serra Calderona Natural Park, a Mediterranean forest ecosystem located between the provinces of València and Castelló (Valencian Country, Spain), has been analysed for almost twenty years. The helminth ecological analysis of 917 A. sylvaticus (675 originating from the burned area and 242 originating from the control area) has been carried out between the 2nd and 18th post-fire years. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Similarly, Milazzo et al [ 56 ] found four helminth species in populations of A. sylvaticus from the riverbed and bank section, but only two were found on the slopes’+ habitat in the studied location in Italy. A greater number of nine helminth species were detected in two areas in Spain in a sample of 917 specimens of A. sylvaticus , but these studies covered an 18-year period [ 57 ]. Our samples were neither spatially nor seasonally balanced among the analyzed species, so nematode diversity illustrates the current situation at the studied localities.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Milazzo et al [ 56 ] found four helminth species in populations of A. sylvaticus from the riverbed and bank section, but only two were found on the slopes’+ habitat in the studied location in Italy. A greater number of nine helminth species were detected in two areas in Spain in a sample of 917 specimens of A. sylvaticus , but these studies covered an 18-year period [ 57 ]. Our samples were neither spatially nor seasonally balanced among the analyzed species, so nematode diversity illustrates the current situation at the studied localities.…”
Section: Discussionmentioning
confidence: 99%
“…and Giardia spp. (Wells et al, 2007;Perec-Matysiak et al, 2015;Fantozzi et al, 2018;Hurtado et al, 2021;Sáez-Durán et al, 2021). Gastrointestinal helminths and protozoal infections can affect survival and reproduction directly by pathological effects (e.g., blood loss, tissue damage) and indirectly through reduction of host condition (e.g., malabsorption of nutrients, predator escape, energetic costs) (Lyles & Dobson, 1993;Scantlebury et al, 2007;Taylor et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, sexual dimorphism in helminth burdens appears to be extremely context dependent (i.e. often seasonal, varying between years and locality specific; Abu-Madi et al, 1998, 2000Behnke et al, 1999;Sáez-Durán et al, 2021;Sweeny et al, 2021a). Despite this, evidence has been provided through a perturbation study that male mice (Apodemus flavicollis) are more important than females in driving H. polygyrus infections in host populations (Ferrari et al, 2004(Ferrari et al, , 2007; see also Luong et al, 2009, for a similar outcome in Peromyscus leucopus infected wih Pterygodermatites peromysci).…”
Section: Introductionmentioning
confidence: 99%
“…Host age ranks highly among those intrinsic factors that are consistently reported as having a marked influence on parasite burdens (Elton et al , 1931; Kisielewska, 1971; Montgomery & Montgomery, 1988, 1989; Abu-Madi et al , 1998; Behnke et al , 1999; Loxton et al , 2016, 2017). In studies where the age of mice was assessed and the mice were subsequently allocated to different age classes, helminth species richness has been found to increase significantly with increasing host age (Montgomery & Montgomery, 1989; Sáez-Durán et al , 2021). The same has been found for the worm burdens of some, but not all individual helminth species (Behnke et al , 1999).…”
Section: Introductionmentioning
confidence: 99%